Measurement in Current Accounting Practice: A Critique. - Chambers, Raymond J. (The Accounting Review, 1972)
The article presents a critique on measurement in current accounting practice. Although "measure," "measuring" and "measurement" occur frequently in expositions of accounting, there is little disciplined measurement in the processes of accounting practice. Current accounting practices have repeatedly been shown to have recourse to so many different quantification rules that a critical examination might be expected to clarify their nature, to show how to discriminate between measurements and other kinds of quantification, and to elucidate the nature of measurement in accounting. The author tries to know whether the amounts obtained by aggregating and taking differences between amounts of such diverse origin are measurements of income, total assets, net equity and so on. Measurement has never been limited to objective measurement in technical literature. Subjective probability measures, utility measures, and many other measures in economics, psychology, sociology, and other areas of social sciences are considerably subjective, yet they are treated as measurement.